The Impact of infrastructure and investment on tourism industry - HTIN, Shar (KDI School, 2017)
Myanmar is the second largest country, has abundance of natural resource, cultural heritages, different kind of tourist attraction, among the ASEAN countries. Investment and infrastructure development have positive relationship between tourism sector development. This paper empirically investigates whether the investment and infrastructure led-growth hyposthesis holds for the ASEAN countries for the period of 2004-2014. A panel data approach is utilized and coefficient estimates are obtaining by using Pooled OLS model, fixed-effects model ans random effect model. As a result, the hyposthesis that investment and infrastructure is conductive to tourism sector development, dependency ratios of dependence and independence variables are verifying base on regression results. As a conclusion, over view of the tourism master plan of Myanmar 2013 to 2020 and policy recommendations for Myanmar’s tourism industry have been conducted base on empirical result, literatures and reports of world tourism organizations in this research.
Thesis(Master) --KDI School:Master of Public Policy,2017